Sala de aula invertida na educação matemática: uma experiência com alunos do 9º ano no ensino de proporcionalidade - Petrina Rubria Nogueira Avelar Tobias (2018)
This research investigated the potential of the Flipped Classroom (FC) in the classes of proportionality of a 9th grade class in a school of the municipal network of Belo HorizonteMG. More specifically, it sought to analyze the students' perceptions regarding FC; the possible influences of the use of videotapes in the process of student-class-teacher interaction in the perspective of the FC. Moreover if this interaction brings elements to collaborate with the teaching of proportionality. The FC, also known internationally as flipped learning, aims to change some organizational paradigms of traditional teaching. The main idea is for the learner to be the protagonist of his own learning, having prior access to the content of the lesson, by either videos, audios, texts, usually with the media resource involving the internet. At school, your classroom becomes a space for discussions with the teacher and colleagues. Thus, what would traditionally be activities to be done at home in the FC will be carried out with the teacher in conjunction with other students, giving them greater opportunities for interactions, sharing and, consequently, learning. The content addressed in this research was proportionality, with the bias of the development of proportional reasoning, seeking to problematize the use of the rule of three as a strategy for solving proportionality problems. It is a very relevant topic in the teaching of Mathematics, since it is present in several situations, both school and non-school. As videotapes were not found on the internet with the desired focus on proportionality teaching, the researcher decided to record her own material and make it available on the internet. The theoretical reference frameworks of this qualitative research were found in Bergmann and Sams (2016) and FLN (2014) to work with the FC; for the teaching of Mathematics, the works of Rational Number Project researchers (RNP), Ponte et al. (2010) and Silvestre (2012). The interactions provided by digital technology resources were found in Borba and Villarreal (2006), Moran (2015) and Kenski (2016). From a qualitative approach, the following instruments of data collection were used: recording in audio and video of observations in classroom; field notes with written record, as well as written and online questionnaire for students. The results point out that the FC is a pedagogical approach to rich opportunities for interactions among students, teachers, the family and the school, which can enhance the teaching of Mathematics. Regarding the pedagogical implications, the importance of the Mathematics teacher to be aware that his teaching practice has much to enrich when he considers his classroom a space of investigation.